2014
DOI: 10.1136/injuryprev-2014-041243
|View full text |Cite
|
Sign up to set email alerts
|

Transport cyclists and road rules: what influences the decisions they make?

Abstract: A transport network needs to facilitate cyclists of all capabilities to reach their required destination in a safe and timely manner, and encourage compliance with the road rules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Few of these collisions were on space designed to be shared by pedestrians and pedal cycles, suggesting a certain amount of riding bicycles on footpaths, which is illegal in the UK. Survey evidence from other settings suggests that cyclists are more likely to break rules when existing infrastructure does not provide safe cycling routes ( Shaw et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few of these collisions were on space designed to be shared by pedestrians and pedal cycles, suggesting a certain amount of riding bicycles on footpaths, which is illegal in the UK. Survey evidence from other settings suggests that cyclists are more likely to break rules when existing infrastructure does not provide safe cycling routes ( Shaw et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although cyclists generally are subject to the same penalties as motor vehicle operators, police are typically reluctant to give moving-violation citations to cyclists (Beck, 2007). Surveys have found that cyclists often believe their safety is enhanced by certain rule violations, such as proceeding prior to a green light in order to improve their visibility to drivers by getting ahead of the traffic (Shaw, Poulos, Hatfield & Rissel, 2014). An alternative rationale for not stopping can be that cyclists are conserving their energy (Fajans & Curry, 2001) and can thereby get up to travel speed in a shorter period of time.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to analyse who drafts the regulations, how and for whom, and how that exposes cyclists (and specifically certain groups of cyclists) to a higher risk. Back to the previous example, if the reasons for cyclists running red lights are related to concerns over their own safety (Shaw et al 2015) this might have to do with the fact that other road users are prioritised or just taken into account by the regulations that put cyclists in risk (Furness 2010).…”
Section: Regulationsmentioning
confidence: 99%